First Physical Examination of the Horton Plains Slender Loris, Loris tardigradus nycticeboides, in 72 Years - Gamage, Saman; Reardon, James T.; Padmalal, U.K.G.K.; Kotagama, S.W. (My University, 2010)
We report here the first close examination in 70 years of the Horton Plains slender loris, Loris tardigradus (lydekkerianus) nycticeboides, previously known only from two collected specimens and a number of sightings from eye-shine. Photographic and morphometric data presented here enable a preliminary assessment of the possible distinctive endomorphic features of this loris in comparison to its sister species and subspecies. This loris clearly demonstrates adaptations to montane forest, as previously suggested from the preserved skins of the holotype and paratype. Confirmation of the continued existence of this loris raises familiar concerns over its taxonomic distinctiveness, its apparent low abundance in a highly fragmented and diminishing habitat, and the actions necessary to eliminate the threats to its survival.